Design and Development an e-Lapor Application to Support Public Complaint Services in Tunjungtirto Village - Fikriansyah Dava Agustyar; Addin Aditya; Siti Aminah; Arif Tirtana (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2023)
The process of public complaints is carried out in a structured manner starting from the central government level to the village government level. In practice, the problem in the public complaint process is when the community as the service user is dissatisfied with the services provided because the complaints submitted are not properly managed or responded to by the complaint officer. The business process for public complaint services in Tunjungtirto village is still carried out conventionally, where people who wish to submit complaints must go to the Village Consultative Body (BPD) office and fill in complaints or aspirations in the community aspirations data book. This is prone to conditions where public complaints are not followed up because they are not properly recorded. This study aims to build a website-based information system with features for complaints, aspirations, and requests for information. The system development method used in this study is the waterfall method where the method is sequential-based software development. The results of application development will be tested at the Tunjungtirto Village BPD office. Based on black box testing, the test results are obtained with a maximum score of 2 for each feature. This shows that in terms of functionality, the application is running according to its purpose. The existence of main features such as displaying complaint data and automatic notifications on the application can assist village officials in managing community complaints and responding to and following up on complaints to the service or escalating complaints to the local government so that community complaints can be managed properly.